Are CAD-CAM milled glass fiber posts better than prefabricated or custom glass fiber posts for endodontically treated teeth? A systematic review with meta-analysis - Campos, Gabriel Barboza; Pellizzer, Eduardo Piza [UNESP]; de Carvalho, Rodrigo Furtado; de Lima, Carolina Oliveira; e Oliveira, Hiskell Francine Fernandes; de Oliveira Limirio, João Pedro Justino [UNESP]; Lemos, Cleidiel Aparecido Araujo (Elsevier, 2024)
Statement of problem: Prefabricated and custom glass fiber posts have been successfully used to reconstruct endodontically treated teeth. However, the performance of computer-aided design and computer-aided manufacture (CAD-CAM) milled glass fiber posts is unclear. Purpose: The purpose of this systematic review with meta-analysis was to compare the fracture and bond strength and cement layer thickness of CAD-CAM milled glass fiber posts with prefabricated or custom glass fiber posts. Material and methods: The protocol was registered in the Open Science Framework (http://osf.io/65jm7). Two reviewers searched the PubMed/MEDLINE, Web of Science, Embase, Scopus, and ProQuest databases for articles up to September 2023. In addition, the reference lists were hand searched. A meta-analysis was performed by using the RevMan 5.4 program. The risk of bias was assessed using the RoBDEMAT tool. Results: After screening, a total of 18 studies were included. The CAD-CAM milled glass fiber posts showed higher fracture strength (P=.02; Standardized Mean Difference [SMD]: 0.57; 95% Confidence Interval [CI]: 0.07 to 1.07), bond strength (P=.010; SMD: 1.07; 95% CI: 0.26 to 1.89), and lower cement layer thickness (P=.009; SMD: −2.94; 95% CI: −5.15 to −0.73) when compared with prefabricated glass fiber posts. However, fracture strength (P=.53; SMD: 0.38; 95% CI: −0.79 to 1.54) and bond strength (P=.90; SMD: −0.05; 95% CI: −0.81 to 0.72) were statistically similar between CAD-CAM milled and custom glass fiber posts. Significant and substantial heterogeneity was observed in all meta-analyzes (P<.01; I>60%). The studies sufficiently reported most domains related to bias, except for randomization of samples, sample size rationale and reporting and operator blinding. Conclusions: CAD-CAM milled and custom glass fiber posts provide an effective and safe option for restoring endodontically treated teeth, especially for weakened teeth or enlarged root canals. However, further well-designed clinical research is recommended to strengthen these findings.